О ПРОСТРАНСТВЕННО-ВРЕМЕННОЙ ОНТОЛОГИИ ТЕОРЕТИЧЕСКОЙ ФИЗИКИ - Будко, В. В. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science")
С позиции диалектического определения свойства сопоставлены субстанциализм и релятивизм в понимании пространства и времени, рассмотрены допустимость собственных пространств, лишенных пространственного фона. Обсуждена гносеологическая природа нетрёхмерных пространств и допространственно-временных объектов. В. В. Будко ПРО ПРОСТІР І ЧАС В ОНТОЛОГІЇ ТЕОРЕТИЧНІЙ ФІЗИЦІ З позиції діалектичного визначення властивості співвіднесені субстанціалізм та реляціонізм у розумінні простору та часу, розглянута припустимість власних просторів без просторового фону. Обговорена гносеологічна природа нетрьохвимірних просторів та допросторово-часових об’эктів. Ключові слова: властивість, субстанціалізм, реляціонізм, простір, власний простір, фоновий простір, первинні об’єкти. V. Budko ABOUT SPACE-TIME ONTOLOGY OF THEORETICAL PHYSICS The opposition of substancialism and relationism in space-time cognition is discussed from the position of dialectical definition of property. It is considered the assumption of background independence that is deprived of spatial background. Gnosiological nature of non-three-dimensional spaces, unspatial and untemporal objects is verified in the article. Key words: property, substancialism, relationism, background independence, background space, primary objects.